Cultural connections: How culturally responsive teaching transforms mathematical learning - Mustafa, Sriyanti; Sari, Vernita; Aflaha, Aflaha; Ahmad, Jamaluddin; Hariyani, Sri (Edelweiss Applied Science and Technology, 2025)
Culturally Responsive Teaching (CRT) integrates students' backgrounds and experiences into the educational process to foster an inclusive and relatable learning environment. This study evaluates the impact of the CRT method on students' mathematics proficiency levels. A quasi-experimental design was employed, involving two instructional phases to assess math abilities before and after applying CRT with 70 eighth-grade students. The data were analyzed using the Wilcoxon Signed-Rank Test to compare test results across evaluation cycles. The findings showed a significant enhancement in students' skills, with the average score increasing from 67.12 in the first cycle to 75.35 in the second. A substantial effect size of 5.11 highlights the effectiveness of CRT in improving mathematical abilities. These findings suggest that CRT not only boosts performance but also narrows achievement gaps among students. By connecting mathematical concepts to students' cultural contexts, CRT enhances comprehension and fosters deeper learning experiences. This study advocates for inclusive curriculum designs that consider student diversity while emphasizing the importance of training educators to implement CRT strategies effectively.